Meningkatkan Hasil Belajar Pak Materi Yesus Mengajarkan Pengampunan Melalui Model PBL Fase C Kelas V di SDN 046413 Barung Kersap - Lisius Bangunta Munthe; Ermina Waruwu (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Improving learning outcomes is a certain competency or ability achieved by students after following the teaching and learning process and includes cognitive, affective and psychomotor skills, which is one of the hopes for every teacher towards their students, the ability to improve the learning outcomes of students at SD Negeri 046413 Barung Kersap is still relatively low, so that linearly student learning outcomes are low, therefore the existing problems will be tried to be overcome with a more interesting learning model, namely PBL. This research aims to find out whether the application of the problem based learning model can improve student learning outcomes in the Catholic Religion Learning process and whether the use of this model can also improve student learning outcomes in Catholic religious learning. The method used is classroom action research with the variable being PBL learning to improve learning outcomes. Data collection techniques using observation, written tests, interviews and documentation were carried out on 11 children. The findings in this research were that in cycle 1 the average score was 36.36% or 45.45%, there were still 2 students who were still at the Eligible stage. In the second cycle the average score was 94.54 or 100% completion of learning outcomes for all students. The increase in learning outcomes increased from 83.63 to 94.54. The implication of this research is that the PBL method can be used by teachers creatively, the teacher's creativity in using the student center learning method brings the completeness of learning outcomes to an increase.